2016
DOI: 10.3389/fmicb.2016.01432
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of an in-House Saponin-Based Extraction Method in Bruker Biotyper Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry System for Identification of Bacterial and Fungal Species in Positively Flagged Blood Cultures

Abstract: We used an in-house saponin-based extraction method to evaluate the performance of the Bruker Biotyper matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) system for the identification of bacteria and fungi in 405 positively flagged blood culture bottles. Results obtained from MALDI-TOF/MS were compared with those obtained using conventional phenotypic identification methods. Of the 405 positively flagged blood culture bottles, 365 showed monomicrobal growth and were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…In addition, increased error rates have been documented for polymicrobial in comparison to monomicrobial BCs in the context of direct MALDI-TOF MS [24]. Only a few studies reported that it may be possible to identify multiple microbial species in polymicrobial BCs by MALDI-TOF MS [16, 19, 25, 26]; however, the correct identification of the two different microorganisms was generally limited to a relatively low percentage of polymicrobial cultures [16, 19, 26]. In a recent study, the performance of the Bruker MBT Sepsityper IVD module was evaluated for the direct identification of microorganisms in polymicrobial BCs by MALDI-TOF MS [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased error rates have been documented for polymicrobial in comparison to monomicrobial BCs in the context of direct MALDI-TOF MS [24]. Only a few studies reported that it may be possible to identify multiple microbial species in polymicrobial BCs by MALDI-TOF MS [16, 19, 25, 26]; however, the correct identification of the two different microorganisms was generally limited to a relatively low percentage of polymicrobial cultures [16, 19, 26]. In a recent study, the performance of the Bruker MBT Sepsityper IVD module was evaluated for the direct identification of microorganisms in polymicrobial BCs by MALDI-TOF MS [26].…”
Section: Discussionmentioning
confidence: 99%
“…365 monomicrobial growth were correctly identified to the species (72.1%) or genus (89.6%) level. The remaining 40 polymicrobial growth showed 82.5% (33/40) of the isolates were correctly identified to the species level and 92.5% (37/40) to the genus level [ 36 ]. Pretreatments to remove non-bacterial proteins are a prerequisite for the successful application of MALDI-TOF MS in patient-derived BCs.…”
Section: Classification and Identification Of Microorganismsmentioning
confidence: 99%
“…Дальнейшие исследования, направленные на сокра щение времени идентификации грибов, стали возмож ными после разработки методов по предварительной обработке положительной гемокультуры с помощью MALDITOF массспектрометрии, минуя этап культивиро вания и ПЦР. Для реализации такого подхода к иден тификации доступны как коммерческие тестсистемы, так и внутренние (in house) алгоритмы, основанные либо на дифференциальном центрифугировании, либо на ис пользовании реагентов для лизиса клеточной стенки грибов (Таблица 4) [16,[19][20][21][22][23].…”
Section: Discussionunclassified